Bond behavior of NSM strips in corroded/cracked reinforced concrete - Al-Akhras, Nabil; Othman, Osama (Frontiers in Built Environment, 2022)
There is limited research on the bond behavior between corrosion-cracked reinforced concrete (RC) and near-surface mounted (NSM) fiber reinforced polymer strips. Therefore, this study was initiated to evaluate the bond behavior between corrosion-cracked RC and NSM strips. The test specimens consist of two concrete prisms (reinforced and plain) mounted from two opposite sides with NSM strips. After 28 days of moist curing, twenty-four specimens were immersed in saline solution and exposed to three accelerated corrosion levels with steel mass loss of 2.2%, 4.1% and 8.1%. The bond behavior was evaluated using double shear pullout test. The study showed that the corrosion cracks increased with the increase of corrosion level. The maximum crack width reached 0.91 mm at corrosion level 3. The mass loss of the corroded reinforcing steel increased from 2.1% for corrosion level 1 to 8.3% for corrosion level 3. The bond strength between NSM strips and corrosion cracked concrete was significantly decreased with maximum reduction of 48% at corrosion level 3. The other bond characteristics including maximum slip, bond toughness and bond stiffness were also decreased with corrosion with percent reduction of (31%, 67% and 35%), respectively. The failure mode of the bond between NSM strips and corrosion cracked concrete was splitting of concrete. Theoretical models were proposed for predicting the bond strength between NSM strips and corrosion cracked concrete based on corrosion level and crack width. The proposed models showed excellent agreement with the experimental results from the current study and the literature.